Cultivating a shared vision with interdisciplinary teams. (10th November 2017) - O'Kane, Brigid P.
ABSTRACT: This paper discusses the rapidly changing field of design and why interdisciplinary partnerships are necessary for solving complex challenges. Specific techniques relating to systems thinking and the creative design process will be introduced. Methodologies in this paper expand and amplify the creative design process, while being inclusive of all members of diverse teams to increase throughput that includes various points of view. Also presented are specific tools to expand the capacity of collaborative groups as they work in harmony towards a shared vision. As creative problem solving teams work together it is important for leadership to relate to diverse perspectives, including creative and scientific disciplines within the team to expand the collective outlook within any group. These leadership tools ultimately enhance the collaborative culture within any organization, which increases productivity leading to more innovative and successful product solutions. GRAPHICAL ABSTRACT: